1996
DOI: 10.1002/etc.5620151119
|View full text |Cite
|
Sign up to set email alerts
|

Limited bioavailability of sediment pah near an aluminum smelter: Contamination does not equal effects

Abstract: Abstract-A Sediment Quality Triad study involving synoptic measures of polycyclic aromatic hydrocarbon (PAH) contamination, toxicity, and resident community (benthic infauna, crab) alteration was conducted to assess impacts from an aluminum smelter discharge. No sediment toxicity was observed, despite extensive testing since 1988 on four test species. Evidence of effects on resident communities was minimal. Effects were not expected in areas Ͼ1 km from the smelter, because PAH concentrations have decreased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 17 publications
(28 reference statements)
4
60
2
Order By: Relevance
“…Details of the organisms than PAHs in a dissolved state. Similar conoccurrence and distribution patterns of PAHs in the clusions were reached by Paine et al (1996), as they fjords are given by NES et al (1995) and N z s & Oug were unable to document toxicity from heavily PAH-(1997PAH-( , 1998. The smelters are located near the heads contaminated sediments near a Canadian aluminium smelter.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Details of the organisms than PAHs in a dissolved state. Similar conoccurrence and distribution patterns of PAHs in the clusions were reached by Paine et al (1996), as they fjords are given by NES et al (1995) and N z s & Oug were unable to document toxicity from heavily PAH-(1997PAH-( , 1998. The smelters are located near the heads contaminated sediments near a Canadian aluminium smelter.…”
Section: Introductionsupporting
confidence: 77%
“…Indeed, studies of PAH profile patterns in the fjords have indicated that the PAHs are resistant to degradation and transformation reactions (Nces & Oug 1997, 1998. Correspondingly, Paine et al (1996) concluded that sediment PAHs present in the form of pitch or coal tar particles in smelter-affected Canadian fjords are of limited bioavailability and do not exhibit toxic effects on the benthic fauna.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their persistence and potential for bioaccumulation, these contaminants are of high concern to environmental risk assessors. Assessment of toxicity and bioaccumulation of HOCs with total extractable contaminant concentration in the sediment (bulk sediment concentration) is unreliable and often provides poor predictions [1,2]. Sediment porewater concentration of HOCs, particularly the freely dissolved porewater concentration, however, has been shown to be a good indicator of bioavailability [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of toxicity and bioaccumulation of HOCs with total extractable contaminant concentration in the sediment (i.e. bulk sediment concentration) is unreliable and often provides poor predictions 31 . Sediment porewater concentration of HOCs, particularly the freely dissolved porewater concentration, however, has been shown to be a good indicator of bioavailability 32,33,34,35 .…”
Section: Introductionmentioning
confidence: 99%